2008
DOI: 10.1183/09031936.00047908
|View full text |Cite
|
Sign up to set email alerts
|

Differential diagnosis and management of focal ground-glass opacities

Abstract: Focal pulmonary ground-glass opacities (GGOs) can be associated with bronchioloalveolar carcinoma. The present retrospective study aimed to test the validity of a multistep approach to discriminate malignant from benign localised (focal) GGOs, identifies useful diagnostic features on computed tomography (CT), and suggests appropriate management guidelines.A stepwise approach, including oral antibiotics, follow-up high-resolution CT (HRCT) 40-60 days later and CT-guided core biopsy, was used. All cases with loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
50
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 32 publications
2
50
1
Order By: Relevance
“…162 In another small study of 40 individuals with subsolid nodules, the diagnostic yield of CT scan-guided core needle biopsy was 84% (16 of 19), but two of three individuals with nondiagnostic results were subsequently found to have cancer. 163 Hence, although TTNB appears to be less sensitive for subsolid than for solid nodules, it is still potentially useful, particularly for individuals who are at higher risk for surgical complications and those who wish to confi rm malignancy before undergoing surgical resection. Although nonsurgical biopsy specimens can confi rm the diagnosis of malignancy preoperatively in some cases, it should not be used to exclude malignancy in view of its imperfect sensitivity and limited negative predictive value.…”
Section: Role Of Nonsurgical Biopsymentioning
confidence: 99%
“…162 In another small study of 40 individuals with subsolid nodules, the diagnostic yield of CT scan-guided core needle biopsy was 84% (16 of 19), but two of three individuals with nondiagnostic results were subsequently found to have cancer. 163 Hence, although TTNB appears to be less sensitive for subsolid than for solid nodules, it is still potentially useful, particularly for individuals who are at higher risk for surgical complications and those who wish to confi rm malignancy before undergoing surgical resection. Although nonsurgical biopsy specimens can confi rm the diagnosis of malignancy preoperatively in some cases, it should not be used to exclude malignancy in view of its imperfect sensitivity and limited negative predictive value.…”
Section: Role Of Nonsurgical Biopsymentioning
confidence: 99%
“…One of the major conclusions in the study by INFANTE et al [1] was that the stepwise approach increased the diagnostic specificity and reduced time to definitive diagnosis. They recommended response to antibiotic trial as the first management step.…”
Section: To the Editorsmentioning
confidence: 99%
“…Because this is a central part of their conclusion, clarification of the question may be helpful. INFANTE et al [1] assumed that lesions with regression after antibiotics treatment were benign GGOs. However, a decrease in size with the appearance of solid components during follow-up has been reported in bronchioloalveolar carcinoma (BAC) and adenocarcinoma with mixed subtype [2].…”
Section: To the Editorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reports from lung cancer screening trials showed that conservative management of pGGN provides optimal balance between risk and benefits. In asymptomatic subjects at high risk of lung cancer, pGGN did not progress to advanced stage lung cancer in several years after first documentation on CT (29)(30)(31)(32). Therefore, long-term active surveillance by low-dose CT (LDCT) is encouraged until the evidence of nodule progression.…”
mentioning
confidence: 99%